A tumor treatment strategy based on biodegradable BSA@ZIF-8 for simultaneously ablating tumors and inhibiting infection. Issue 6 (11th July 2018) - Wu, Qiong; Li, Mei; Tan, Longfei; Yu, Jie; Chen, Zengzhen; Su, Liuhui; Ren, Xiangling; Fu, Changhui; Ren, Jun; Li, Laifeng; Cao, Feng; Liang, Ping; et al.
Abstract : Biodegradable BSA@ZIF-8 can treat cancer by tumor microwave ablation, while simultaneously inhibiting bacteria and resisting infection. Abstract : Studies have shown a clear correlation between cancer incidence and infection, and cancer treatment can also trigger infection so as to lead to an inflammatory response. In this case, we have designed a new tumor treatment strategy based on biodegradable BSA@ZIF-8 for simultaneously ablating tumors and inhibiting infection. This biodegradable ZIF contains abundant porous structures, showing increased absorption of ions and inelastic collisions. A large amount of frictional heat produced by the collisions results in increased tumor cell death under microwave irradiation. This can effectively inhibit tumor growth in mice by microwave ablation with a good anti-tumor effect (95.4%). Intriguingly, the Zn 2+ released from the degradation of BSA@ZIF-8 causes damage to bacterial cell walls, and destruction of the metabolism and structure of the membrane, leading to bacterial cell death, and ultimately achieving good antibacterial properties. Moreover, BSA@ZIF-8 is biodegradable without long-term toxicity in vivo . The in vivo experimental results show that BSA@ZIF-8 can protect 80% of the mice from lethal challenge with tumors and the accompanying infection. Overall, we present a novel strategy using biodegradable ZIFs for microwave ablation therapy with simultaneous antibacterial and anti-infection effects for the first time, which has achieved good tumor treatment outcomes.